BSN: First photometric light curve analysis of two W-type contact binary systems OP Boo and V0511 Cam - Poro, A.; Tanriver, M.; Keskin, A.; Bulut, A.; Rabieefar, S.; Gharghabi, M. M.; Walter, F.; Holy, S.
This study presented the first light curve analysis of the OP Boo and V0511 Cam binary stars, which was conducted in the frame of the Binary Systems of South and North (BSN) Project. Photometric ground-based observations were conducted with standard filters at two observatories in the Czech Republic. We computed a new ephemeris for each of the systems using our extracted times of minima, TESS data, and additional literature. Linear fits for O-C diagrams of both systems were considered using the Markov Chain Monte Carlo (MCMC) method. The light curves were analyzed using the Wilson-Devinney (WD) binary code combined with the Monte Carlo (MC) simulation. The light curve solutions of both target systems required a cold starspot. The absolute parameters of the systems were calculated by using a P - M parameter relationship. The positions of the systems were also depicted on the Hertzsprung-Russell (HR), P - L, logMtot - logJ0, and T - M diagrams. The hotter component in both systems is determined to be a more massive star. Therefore, it can be concluded that both systems are W-type contact binary systems.
Keywords: Biinaries